The Influence Of Marketing Mix On Customer Satisfaction Of Online Transportation Services Maxim Bike In Bengkulu City - Aliano, Dio; Monique, Eska Prima; Rydarto, Dennis (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2025)
Maxim Bike is an online transportation service that is part of the Maxim company which offers application-based transportation services in various cities in Indonesia, especially in Bengkulu City, this research aims to find out how much influence Marketing Mix has on customer satisfaction of Maxim Bike online transportation services. This type of research uses quantitative research. The analysis method in this type of research uses validity test, reliability test, classical assumption test, multiple linear regression test, coefficient of determination and hypothesis testing. The number of samples studied amounted to 80 users of Maxim Bike transportation services. The results of the multiple linear regression analysis are the equation Y = 7,181 + -0.054 X1 + 0.116X2 + 0.152X3 + 0.054X4 + -0.100X5 + 0.241X6 + 0.163X7 + e. From the results of testing the t test hypothesis, it is known that the variable Product (X1) 0.610> 0.05, Price (X2) 0.118> 0.05, Promotion (X4) 0.482> 0.05, People (X5) 0.360> 0.05, Process (X7) 0.335> 0.05 has no significant effect because the significant value is greater than 0.05, while for the variable Place (X3) 0.025 < 0.05, Physical evidence (X6) 0.008 < 0.05 has a significant effect. For the f test test, a significant value of 0.000 <0.05 is generated, this indicates that the marketing mix has an effect simultaneously or together.